Sexual dysfunction among post-partum women and its associated risk factors in Primary Care Clinics in Kuantan, Pahang - Jamani, Nurjasmine Aida; Khalid, Nur Nadrah; Abd. Aziz, Karimah Hanim (2019)
Introduction: Childbirth is one of the recognized risk factors for female sexual dysfunction (FSD). Despite high prevalence of female sexual dysfunction worldwide, there is very limited data concerning sexual dysfunction in postpartum women. The aim of our study is to determine the prevalence of FSD and its subtypes among postpartum women in primary health clinics in Kuantan, Pahang. Materials and method: This cross-sectional study was conducted at 9 primary health clinics located at urban and suburban areas in Kuantan, Pahang from February to June 2018. A validated Malay version of Female Sexual Function Index (MVFSFI) was used to assess FSD. A total of 372 women who have given livebirth within 6 weeks to 6 months were invited to participate in this study. Results: The prevalence of FSD among postpartum women in the primary care population was 35.5%. The most common reported sexual dysfunction was lubrication disorder (85.6%), followed by desire disorder (69.7%), pain disorder (62.9%), arousal disorder (11.0%), orgasmic disorder (9.7%) and satisfaction disorder (7.3%). Our results showed that level of education (aOR= 1.71 95% CI 1.04, 2.84) and use of contraception (aOR= 0.58 95% CI 0.36, 0.95) were associated with postpartum sexual dysfunction. Conclusion: The prevalence of FSD among postpartum women in primary care clinics in Kuantan, Pahang was high. Thus, it is important for the healthcare providers to address this issue during postpartum consultation at primary care level.